Jaringan Internet Untuk Upload Video Menggunakan Provider Telkomsel - Anisa, Anisa; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Internet Service Providers (ISP), better known as internet service providers, are manufacturers or institutions that provide internet connection services and other related services. To monitor the stability of the Provider network, a Quality of Service (QoS) parameter is needed as a standard for testing the quality of internet services, for example when uploading videos, the traffic load on the internet network will increase. . Quality of Service (QoS) is carried out by monitoring the access speed of Telkomsel providers with the delay parameter as a determining point. The results of Quality of Service research when uploading videos with 360p resolution for 3 days using a Telkomsel provider in the morning obtained the lowest delay value with an average of 1.17 milliseconds (ms) and the highest delay value was obtained during the day 1.81 milliseconds (ms). with good quality according to TIPHON standard. From these results it can be concluded that the higher the delay value of a data, the slower the network speed.Keywords : ISP, Upload, Delay, QoS